Taxing women : with a new preface - McCaffery, Edward J. (Chicago : University of Chicago Press, 1999)
Taxing Women comprises both an insightful, critical analysis of the gender biases in current tax laws and a wake-up call for all those concerned with gender justice to pay more attention to the pervasive impact of such laws. Providing real-life examples, Edward McCaffery shows how tax laws are actually written to punish married couples who file jointly. No dual-income household can afford not to read this book before filing their taxes.'Taxing Women is a must-have primer for any woman who wants to understand how our current tax system affects her family's economic condition. In plain English, McCaffery explains how the tax code stacks the deck against women and why it's in women's economic interest to lead the next great tax rebellion. -- Provided by publisher
INTRODUCTION: The Basic Story -- Smaller Stories -- Not Just Married with Children -- Expanding the Story -- Some Answers -- A Quick Sketch -- Choices and Audience -- PART ONE-- GETTING MARRIED, TAX STYLE: Women on the Margin -- A Bit of History, 1913 to 1948 -- Still His Story, 1948 to the Present -- PART TWO-- BEYOND JOINT FILING: GETTING WORSE: Social Security Isn't What It Looks to Be -- Piling It on the Margin -- Taxing Families -- PART THREE-- THEORY, PRACTICE, AND RHETORIC: ON (NOT) GETTING IT: Some Taxing Hope -- Not Just the Facts -- The Curious Nostalgia of the Contracts -- PART FOUR-- BEYOND TAX: GETTING WORSE, STILL: Not Just Tax -- Not Just the Gender Gap -- On Doing Nothing, and Some Things to Do
Includes bibliographical references (pages 289-302) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Women -- Taxation -- Law and legislation -- United States; Women -- Taxation -- United States; Femmes -- Impôts -- États-Unis.; BUSINESS & ECONOMICS -- International -- Taxation; Women -- Taxation; Women -- Taxation -- Law and legislation; United States